Multiple Social Identities Enhance Health Post-Retirement Because They Are a Basis for Giving Social Support - Steffens, Niklas K.; Jetten, Jolanda; Haslam, Catherine; Cruwys, Tegan; Haslam, S. Alexander (Frontiers in Psychology, 2016)
We examine the extent to which multiple social identities are associated with enhanced health and well-being in retirement because they provide a basis for giving and receiving social support. Results from a cross-sectional study show that retirees (N = 171) who had multiple social identities following (but not prior to) retirement report being (a) more satisfied with retirement, (b) in better health, and (c) more satisfied with life in general. Furthermore, mediation analyses revealed an indirect path from multiple social identities to greater satisfaction with retirement and better health through greater provision, but not receipt, of social support to others. These findings are the first to point to the value of multiple group membership post-retirement as a basis for increased opportunities to give meaningful support to others. We discuss the theoretical and practical implications for the management of multiple identities in the process of significant life transitions such as retirement.